Mining Metagenomic Data Sets for Ancient DNA: Recommended Protocols for Authentication. Issue 8 (August 2017) - Key, Felix M.; Posth, Cosimo; Krause, Johannes; Herbig, Alexander; Bos, Kirsten I.
Abstract : While a comparatively young area of research, investigations relying on ancient DNA data have been highly valuable in revealing snapshots of genetic variation in both the recent and the not-so-recent past. Born out of a tradition of single-locus PCR-based approaches that often target individual species, stringent criteria for both data acquisition and analysis were introduced early to establish high standards of data quality. Today, the immense volume of data made available through next-generation sequencing has significantly increased the analytical resolution offered by processing ancient tissues and permits parallel analyses of host and microbial communities. The adoption of this new approach to data acquisition, however, requires an accompanying update on methods of DNA authentication, especially given that ancient molecules are expected to exist in low proportions in archaeological material, where an environmental signal is likely to dominate. In this review, we provide a summary of recent data authentication approaches that have been successfully used to distinguish between endogenous and nonendogenous DNA sequences in metagenomic data sets. While our discussion mostly centers on the detection of ancient human and ancient bacterial pathogen DNA, their applicability is far wider. Trends: NGS has revolutionized ancient DNA research by permitting the evaluation of short molecules that could not be accessed via PCR. Damage profiles can now be constructed from ancient molecules to confirm their authenticity. Analyses have quickly moved from single-locus identifications to genome-level resolution and laboratory procedures have been refined to permit an ever-increasing sample throughput. Ancient human DNA authentication has the inherent challenge of distinguishing between endogenous DNAs and those stemming from modern human contamination. The growing field of ancient pathogen research requires specialized approaches to distinguish true positive identifications from sequences that stem from the (often unknown) environmental background.